Potentials of Hydrocarbon Utilization by Wood-Digesting Bacteria isolated from the Lagos Lagoon, Nigeria. - Buraimoh, Olanike Maria; Ogunyemi, Adewale Kayode; Oyegbite, Isaac Edward; Amund, Olukayode Oladipo; Ilori, Matthew Olusoji (Journal of Tropical Life Science, 2020)
Introduction: There is a continuous search for environmentalâ€“friendly methods to address oil-polluted environments, hence this study aimed to establish the potential of using tropical estuarine bacterial strains for degradation of crude oil in polluted environment. Microbial degradation of hydrocarbons has been considered a promising, natural, less toxic and cost-effective technology. Lignocellulose-utilizing bacterial strains (Bacillus megaterium strain NOB, Streptomyces pseudogriseolus strain EOB and Paenibacillus sp. strains ROB) were isolated from decomposing wood residues in a tropical lagoon. They were identified on the basis of morphological and biochemical characteristics, observation under scanning electron microscope and 16S rRNA gene sequencing. Methods; Microbial growth assessment coupled with biosurfactant production were performed in triplicates under aerobic batch conditions in Erlenmeyer flasks containing mineral salts medium fortified with trace elements and crude oil as the sole carbon source.Â  Results: The generation times of strains NOB, EOB and ROB were 28.3, 44.9 and 46.8 h; with specific growth rates of 14.2, 8.9 and 8.6 h-1,respectively on crude oil. Gas chromatographic analysis of residual hydrocarbons from the growth cultures of isolates revealed that the three strains had degraded the oil by 89.34, 86.33 and 79.37%, respectively at the end of 21 day. The cell hydrophobicity of the bacterial strains also reached 83.6, 79.4 and 69.4%, respectively. Conclusion: The results from this study suggest that wood-digesting bacterial strains from a tropical lagoon possess hydrocarbon utilization capabilities. They could therefore have potentials for deployment in the bioremediation of petrochemical spills in polluted environments.